Planning, provision and perpetuity of deathscapes—Past and future trends and the impact for city planners. (September 2016) - Davies, P.J.; Bennett, G.
Graphical abstract: Highlights: Voluntary renewable tenure should be a transition to mandatory and retrospective renewal. Land use zonings need greater clarity to define future areas for cemeteries and crematoria. Informal burials and cremation 'factories' are being driven by cost and shifting social values. Abstract: Cemeteries present somewhat of a planning conundrum. They are considered an essential piece of social infrastructure, a sacred and permanent fixture in the landscape. Cemeteries also have the capacity to incite substantial community and political opposition when proposals arise to construct a new facility or to expand or extend the use of existing spaces. The social relevance of cemeteries is being tested by lower visitation rates and changing interment practices such as 'no service' cremations, often linked to the emergence of cremation factories, and informal burials. Renewable tenure of individual burial sites and wholesale cemetery renewal is potentially a pragmatic land use outcome to accommodate an ever-increasing demand. However, cemetery renewal as a societal choice has been proven too socially and politically controversial. This has meant the land provided for cemeteries is locked up in a 'perpetual care' obligation, and sites are often subsequently abandoned. This paper examines how the private and public sectors undertake cemetery planning in Sydney, Australia. It explores the role and impact of legislative reform, how this intersects with strategic land use planning and emerging trends that may influence the direction for this sector.